Characteristics of menstrual disorders and reproductive hormones in women with epilepsy at an Indonesian national referral hospital - Octaviana, Fitri; Sumapraja, Kanadi; Wiratman, Winnugroho; Indrawati, Luh Ari; Budikayanti, Astri (Frontiers in Neurology, 2022)
Objective: Menstrual disorders are more common in women with epilepsy than in those without epilepsy. This study aimed to examine the characteristics of reproductive function in women with epilepsy at an Indonesian National Referral Hospital. Methods: A case-control study was conducted from March 2020 to March 2021. Women with and without epilepsy aged ≥18 years were enrolled. All women were premenopausal before epilepsy diagnosis. Data on demographic characteristics, menstrual profiles, epileptic syndrome, seizure type, seizure frequency, etiology, localization, and anticonvulsant medication were collected. Hormone levels (follicle stimulating hormone, luteinizing hormone, prolactin, and estradiol) were measured. Results: A total of 72 women with and 50 without epilepsy (controls) were included. Dysmenorrhea was more common in women with epilepsy than in those without (59.7% vs. 20%, p<0.001; odds ratio: 5.93 [95% confidence interval: 2.6–13.7]). Marriage rates were higher in women without epilepsy (82% vs. 45.8%, p<0.001). No difference was found in hormone levels between the groups. The frequency of seizures was associated with prolactin and estradiol levels (p<0.001). Polytherapy with clobazam was correlated with menstrual cycle regularity. In women with epilepsy with menstrual disorders, valproic acid was associated with higher estradiol levels (p=0.001) and lamotrigine with lower follicle stimulating hormone levels (p=0.008). Significance: Women with epilepsy experienced more dysmenorrhea. A higher frequency of seizures correlated with lower prolactin and estradiol levels. Polytherapy with clobazam was associated with irregular menstrual cycles, while valproic acid and lamotrigine was associated with estradiol and follicle stimulating hormone levels. Keywords: menstrual disorders, dysmenorrhea, epilepsy, women, reproductive hormones